Repeatability estimation for egg and chick production in meat-type chickens - Custódio, Randolfo William Silvestre (Pesquisa Agropecuaria Brasileira, 1997)
Repeatabilities were estimated for hatchability of fertile eggs (ECLOD), hatchability of all eggs set (NASC) and percentage of lay (POST). Data from three meat-type chicken populations were utilized in two experiments. Females were artificially inseminated, twice a week, with a pool semen of more than 20 males from their own populations. Average repeatability in the first and second experiments were all significant (P<0.01) and equal to 0.10±0.06 and 0.17±0.08 for ECLOD, 0.16±0.06 and 0.16±0.08 for NASC, 0.33±0.07 and 0.33±0.09 for POST, respectively. It was concluded that about 30 females was an appropriate number to obtain satisfactory estimates of repeatabilities for these traits. Repeatabilities were utilized as a superior limit of the heritabilities in establishing adequate numbers of measures that would give sound genetic responses when selecting females based on their own performances. The expected increase in genetic gain from selection, as a function of the number of hatches used for evaluating ECLOD, NASC and POST, was considerable as compared to the estimates obtained with only one measurement. About 103 days for measuring individual egg production was satisfactory for reaching a repeatability estimate of 0.40. For hatchability of all eggs set and hatchability of fertile eggs, at least 150 days would be necessary to attain 0.20 for ECLOD and 0.30 for NASC.